A Note On The Quasi-Conformal And M-Projective Curvature Tensor Of A Semi-Symmetric Recurrent Metric Connection On A Riemannian Manifold - Rajesh Kumar; Jagannath Chowdhury (Süleyman Demirel Üniversitesi Fen-Edebiyat Fakültesi Fen Dergisi, 2013)
Abstract: In the present note we have considered Mn to be a Riemannian manifold admitting a semi-symmetric recurrent metric connection. The aim of the present paper is to obtain the conditions under which the quasi-conformal curvature tensor and M-projective curvature tensor of semi-symmetric recurrent metric connection and the Riemannian connection to be equal.